Theoretical framework to predict the balance of strength-ductility in graphene/metal nanocomposites. (15th April 2023) - Sun, Yang; Li, Ang; Zhang, Wei; Liu, Mabao
Highlights: Graphite nanoplatelet reinforced TC4 composites with various grain sizes and appropriate interphase properties to simultaneously enhance strength and ductility are facilely prepared. A multiscale theoretical framework for predicted the entire stress–strain relations of graphene/metal nanocomposites with grain sizes and dual hard/soft interphase effects is developed. The overall mechanical properties considering grain sizes, interphase effects and progressive damage have a good accuracy against experimental results. Both size distribution and geometrical size factor of graphite nanoplatelet contribute to interphase effects. Abstract: Grain size of metal phase and interphase property play an important role in enhancing the strength-ductility synergy of graphene/metal nanocomposites. In this work, we propose a theoretical framework to investigate the effects of different grain sizes and interphase properties on the strength and ductility of graphite nanoplatelet (GNP)/metal nanocomposites. The GNP/TC4 nanocomposites with various grain sizes are first fabricated by powder metallurgy. On the basis of the interphase model, dislocation density-based constitutive law, the field fluctuation method, and continuous damage theory, the micromechanics model for evaluating the balanced strength and ductility is established. Simultaneously, the accuracy of theoretical model is demonstrated by the tensile experiment of GNP/TC4 nanocomposites. To reveal how the strength and ductility of graphene/metal nanocomposites are enhanced synchronously, the influences of the major micromechanical variables including grain size of metal matrix, volume fraction and elastic modulus of interphase, as well as size distribution of GNPs on the strength and ductility are quantitatively assessed. Overall, the present work highlights the mechanisms governing the macro-mechanical properties of graphene/metal nanocomposites and furnishes a powerful analytical tool for their design.